PENDAMPINGAN MANAJEMEN RISIKO BAGI PENJAMINAN MUTU FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN, UNIVERSITAS ISLAM LAMONGAN - Leny Yuanita; Wahyu Budi Sabtiawan; Lucky Rachmawati; Ari Widayanti; Vega Candra Dinata; Ambar Kusumaningsih; Eny Sulistyowati; Janet Trineke Manoy; Arik Triarso (Universitas Negeri Surabaya, 2026)
Higher education institutions face challenges in both academic and non-academic fields due to dynamic environmental and regulatory changes. Universities must be adaptive through effective implementation of risk management (RM) to achieve organizational goals. The community service (PKM) partner in this program is the Faculty of Teacher Training and Education (FKIP) at the Islamic University of Lamongan (UNISLA), which is in the early stage of implementing RM. Based on the experience of the Internal Quality Assurance Agency (BPI) of Universitas Negeri Surabaya, a *knowledge-sharing* activity was conducted to enhance RM maturity at UNISLA. The aim of this program is to improve the partner’s ability and skills in applying RM effectively. The PKM program began in March 2025 and was carried out in four stages: preparation, material presentation, training and mentoring on risk identification, and evaluation. The activities took place from May 15 to September 26, 2025, involving 12 members of UNISLA’s quality assurance team. The results showed a significant improvement in RM understanding (p<0.001), with the average score increasing from 45.70 to 69.60. Participants were also able to complete the risk register, develop an organizational structure, and draft RM guidelines. Participants responded positively to the mentoring activities. The PKM outputs include an activity video, online media publication, intellectual property rights (IPR), a memorandum of understanding (MoU), and an article submitted to an international reputable journal. Keywords: Risk Management, Mentoring, Islamic University of Lamongan